STUDENTS’ READINESS AND PERCEPTION ON BLENDED LEARNING IMPLEMENTATION IN ESP CLASSROOM - Salim, Mochammad Abdullah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The introduction of blended learning in ELT has brought various positive impacts to the leaners. However, a study related to the utilization of blended learning in ESP environment is rarely undertaken. Thus, this paper provides an investigation of blended learning implementation in ESP classroom, a teaching approach that integrates between internet-based activity and the traditional daily teaching and learning. The investigation was carried out in the form of survey involving 200 ESP students as the samples of university of Muhammadiah Malang. The finding explored that the majority of the students have been ready to implement the blended learning in the learning process. it was also found that most of the students showed good perception on the blended learning implementation.